Artificial Intelligence in Business: A Literature Review from maqasid al-Shariah Perspective’s (Lembaga Contrarius Indonesia, 2026)
Artificial intelligence (AI) has emerged as one of the key drivers of global business transformation. Its use across various sectors from marketing, logistics, finance, healthcare and e-commerce has created immense opportunities for innovation and economic growth. However, its deployment also portends foundational challenges, including inequalities wrought by algorithmic bias, the threat of job loss via automation and the pressing need for institutional structures that safeguard society from manipulation by technology. From the Islamic perspective, all these issues have to be examined in terms of maqasid al-Shariah that is concerned with the safeguard of religion (Hifz al-Dīn), life (Hifz al-Nafs), intellect (Hifz al-'Aql), lineage (Hifz al-Nasl) and property (Hifz al-Māl). Using a narrative review, this paper examines AI literature from 2016–2025, a period reflecting AI’s transition into a major socio-economic force. The review focuses on workforce, ethics and governance; as these domains capture the most consequential impacts of AI and directly correspond to maqasid al-Shariah principles. The study illustrates that while AI has tremendous potential to make a contribution to productivity and economic sustainability, its beneficial applications can be utilized to the full only if combined with maqaṣid-inspired ethical frameworks supported by robust government policies. Beyond the Islamic context, this study contributes to the global discourse on ethical AI governance by offering a value-based framework that complements existing secular and regulatory approaches. Accordingly, the paper recommends the development of an Islamic AI ethical framework, sustained investment in workforce upskilling and reskilling and the formulation of maqaṣid-based public policies to ensure that AI technologies genuinely serve the broader interests of humanity.